PERMINTAAN MAAF DALAM BAHASA INGGRIS AUSTRALIA DAN BAHASA INDONESIA SEBUAH KAJIAN PRAGMATIK LINTAS BUDAYA TENTANG STRATEGI KESOPANAN BERBAHASA - , subandi, Prof. Dr. I Dewa Putu Wijana, S.U., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study examines the apology in Australian English and in Indonesian. This study applied a pragmatic approach that is descriptive study conducted with considering the viewpoint of the language use in a particular context. it explains the forms used to express an apology in Australian English and Indonesian, as well as to explain the differences and similarities of language politeness strategies used to express an apology from the point of view of the Australian English and of the Indonesian culture . To learn apology in the Australian English and the Indonesian needs data of speech act of apology. It was collected using discourse complementary text (DCT) by taking 14 Australian English speakers and 14 Indonesian speakers ( Javanese ) as respondents . While, in analyzing the data, it used pragmatic match method. From the results of the data analysis found that in terms of the form of expression of apology used, the two speakers realized the apology stated explicitly and implicitly as